Changes in ownership forms and role of institutional investors in governing public companies in Malaysia: a research note - Annuar, Hairul Azlan (Emerald Group Publishing Limited, 2015)
Purpose The purpose of this paper is to ascertain whether different types of institutional investor in Malaysia are involved in the corporate governance of their investee companies, and, if yes, to what extent is the level of the involvement.